Green building - experiences in Japan and developed countries. Recommendation for Vietnam : Luận văn ThS. Kỹ thuật hạ tầng - Nguyen, Anh Tuan (2019)
CHAPTER 1: GENERAL OVERVIEWS. CHAPTER 2: EXPERIENCES IN JAPAN AND DEVELOPED. COUNTRIES IN GREEN BUILDING. CHAPTER 3: RECOMMENDATION FOR VIETNAM